Association between homocysteine levels and cognition in late-life depression - Fan, Ning; Zhang, Qi; Zhao, Wenxuan; Yun, Yajun; Zhang, Meng; Wang, Yongqian; Wang, Xinrui; Sang, Xufang; Zhou, Bo; An, Huimei; Fan, Fengmei; Han, Xiaole; et al. (Frontiers in Psychiatry, 2025)
BackgroundCognitive impairment frequently occurs in patients with late-life depression (LLD) and could be associated with variations in homocysteine (Hcy) levels. This study aimed to evaluate the relationship between Hcy levels and cognitive function, with particular attention on how baseline cognitive status may impact this relationship.MethodsThis cross-sectional study included 60 patients with LLD meeting Diagnostic and Statistical Manual of Mental Disorders, V Edition (DSM-5) diagnostic criteria and 46 age-matched healthy controls (HCs). Participants were excluded if they had severe physical illnesses. Cognitive function was assessed using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) scale and Mini-Mental State Examination (MMSE). Hcy levels were determined.ResultsCompared to HCs, LLD patients demonstrated significant impairment across all RBANS subdomains except language (p < 0.001), with elevated Hcy levels (t = 2.688, p = 0.008). Hcy was negatively correlated with cognition, and there was possible evidence of an interaction between Hcy and depression severity, such that this association intensified as depression severity increased (interaction β = 1.385, 95% confidence interval: 0.006–0.589, p = 0.046).Subgroup analysis showed that the negative correlation between Hcy and cognition was exclusively observed in the N-MMSE group (Normal MMSE scores, ≥26; p < 0.05).LimitationsThe small sample size and lack of ethnic diversity may limit the generalizability of our results.ConclusionPatients with LLD often exhibit cognitive impairment and elevated Hcy levels. Notably, the association between Hcy and cognitive function is influenced by the patients’ baseline cognitive status. This study offers novel insights into the mechanisms underlying cognitive impairment in patients with depression.